Oculomotor Dysfunction in Parkinson's Disease - Kennard, C; Nachev, P (Humana Press Inc., 2013)
A disturbance of the oculomotor system is the principal neuro-ophthalmological manifestation of Parkinson's disease (PD). Although rarely symptomatic, this disturbance is a valuable subject for study because it illuminates two areas of wider interest: first, the nature of the motor and cognitive dysfunction in PD, and second, the role of the basal ganglia in oculomotor control. In this chapter, we shall give a brief overview of the anatomy and physiology of eye movements before proceeding to a detailed examination of the oculomotor abnormalities in patients with PD. © Springer Science+Business Media New York 2013.